Men and women farmers’ perceptions of adopting improved diets for pigs in Uganda: decision‑making, income allocation, and intra‑household strategies that mitigate relative disadvantage - Carter, Natalie A.; Humphries, S.; Grace, Delia; Ouma, Emily A.; Dewey, Catherine E. (Springer, 2017)
Background: The roles and responsibilities of men and women in east African smallholder pig-raising households and the entitlements each can claim from pig-enterprise income are unknown. The article is a qualitative genderand- household-head-disaggregated exploration of Ugandan smallholder pig farmers’ perceptions. Asset ownership, control, and access; division of labour; and decision-making related to pig rearing and pig-enterprise income are presented in the context of the potential impact of adopting improved diets for pigs (a productivity improvement). Results: Potential benefits of improved diet adoption included faster pig growth; increased farmer income and pig population; new on-farm employment and produce market opportunities; and improved pig market opportunities and family- and community-level well-being. Contradictory views about the potential impact of diet adoption on labour requirements and feed costs, and the inclusion of seasonal, home-grown ingredients were expressed. Concerns about people and pigs competing for food and personal safety were also voiced. Women allocated pig-enterprise income to provide for their children, household, and extended family, and spent only the remaining income on themselves. Men allocated income to meet personal needs, and to provide for their children, wife, second wife/family, extended family, and lovers. Men and women in female-headed households (WFHH) had overt decision-making ability over the pig enterprise and pig-enterprise income. Some women in male-headed households (WMHH) had overt decision-making ability over the pig enterprise and pig-enterprise income when their husband allowed it, or failed to provide, or was away. Pig ownership and labour investment by WMHH did not guarantee that women had decisionmaking ability or benefitted from pig-enterprise income. Some WMHH employed covert strategies which mitigated their relative disadvantage. Threat of domestic violence inhibited the decision-making ability of WMHH. Polygyny reduced intra-household communication transparency. Conclusions: Diet adoption could benefit smallholder pig-raising households and farming communities, but lack of funds and human/pig food competition could limit adoption. Men, WFHH, and some WMHH had overt decisionmaking ability over the pig enterprise and pig-enterprise income. Men allocated income to benefit themselves, and their multiple families and lovers. Women allocated income to benefit their families and spent only surplus income on themselves. Women employed covert strategies to mitigate their relative disadvantage.